Photoredox-catalyzed decarboxylative alkylation/cyclization of alkynylphosphine oxides: a metal- and oxidant-free method for accessing benzo[b]phosphole oxides. Issue 2 (7th December 2018) - Liu, Lixin; Dong, Jianyu; Yan, Yani; Yin, Shuang-Feng; Han, Li-Biao; Zhou, Yongbo
Abstract : By photoredox-catalysis, alkylation/aryl cyclization of alkynylphosphine oxides towards benzo[ b ]phospholes has been realized under metal- and oxidant-free conditions at room temperature. Abstract : By photoredox-catalysis, alkylation/aryl C–H cyclization of readily available alkynylphosphine oxides towards benzo[ b ]phospholes has been realized under metal- and oxidant-free conditions at room temperature. This reaction readily incorporates various functionalized alkyl groups into the benzo[ b ]phosphole skeletons, representing a mild and versatile tool for the preparation of valuable phosphole compounds.